From Grief to Superbia: the Myth of Niobe in Greek and Roman Funerary Art - Leshem, Bar (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The Greek myth of Niobe was known in the ancient world both by literary sources and visual representations. Both in Ancient Greece and in Ancient Rome, the myth was represented, alongside a variety forms of art, in funerary art, but in a different manner during each period of time. In Ancient Greece, the myth was represented on Apulian and South Italian vases, portraying the finale scene of the myth: Niobe’s petrification. In Ancient Rome, a shift is visible: the portrayal of the scene of the killing of Niobe’s children on sarcophagi reliefs. The aim of this paper is to follow the iconography of each culture and to understand the reason for the shift in representation, while comparing the two main media forms.